Conflicts between Gold Mining Companies and Their Host Communities; the Case of Anglogold Ashanti in the Tarkwa-Nsuaem Municipality - Elizabeth-Jane, T. (University Of Ghana, 2015)
It is expected that there will be a cordial relationship between the mining companies and their host communities due to their (gold mining companies and host communities) supposed interdependence, However, the extraction of gold has caused widespread disaffection between gold mining companies and their host communities leading to significant backlash and occasionally, violent conflict. The research therefore, sorts to find the causes of the conflict between gold mining companies and their host communities using AngloGold Ashanti in the Tarkwa - Nsuaem Municipality as a case. The study was conducted to critically examine the issues that lead to conflict between gold mining companies and their host communities. The study used both quantitative and qualitative methods. It also used both primary and secondary sources of data. The study employed stratified and simple random sampling methods under probability sampling and purposive, quota and volunteer sampling under the non-probability sampling methods. The sampling totaled 135; 100 questionnaire respondents, 30 focus group discussants and 5 interviewees. SPSS software and content analysis were used to analyze the data. The study revealed the causes of the conflict to include; The Lack of and Inadequate Information, Selfishness on the part of the Mining Companies, Failed Promises, the Disregard for Local Authorities, Aggressive Nature of Mining Companies, Lack of Maintenance and the Negative Effects of Mining Operations on the Community. The study further revealed; the Disregard of Safety Rules By The Host Community, and Over Dependence on Mining Company as the Cause Of Conflict and lastly the Issue of Speculative Activity and In-Migration. The study therefore recommended education on; Mining laws, Reforms and Compensation, the Effects of Mining Operations, Traditional norms and Taboos and the of Importance Formal Education. Effective Communication and Consultation between mining companies and their host communities, Mining Companies and host communities should desist from Creating Dependency and the people should desist from Engaging in Speculative Activities.
Thesis,(MPhil)-University Of Ghana, 2015
Keywords: Gold Mining; Company; Anglogold Ashanti